PENGARUH EDUKASI VIDEO ANIMASI TERHADAP PENINGKATAN PENGETAHUAN SADARI PADA SANTRIWATI MAS MADINATUL MUNAWWAROH BUKITTINGGI - Afnas, Nur Hidayah; Nanda, Sesmi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract : Currently, breast cancer is a serious threat in the world and is also a major problem in Indonesia and other countries. Breast cancer is the main cause of morbidity and mortality among women. Breast cancer is the second highest case in the world reaching 2098 million people (11.6%), and 627000 of them (6.6%) cause death. The highest prevalence of breast cancer in Indonesia is in the city of Yogyakarta, which is 2.4% followed by East Kalimantan Province at 1.0% and West Sumatra at 0.9%. While in the province of North Sumatra it is 0.4%. Generally, deaths from breast cancer occur due to late treatment where breast cancer sufferers come already with stages III and IV (advanced stages), so that public health actions or interventions need to be taken through breast self-examination (sadari). The purpose of this study was to determine the effect of animated video education on increasing self-examination knowledge in female students of MAS Madinatul Munawwaroh Bukittinggi. This type of research is quantitative research with a Pre-Experimental design with a One Group Pretest Posttest design. The population in this study were all female students of MAS Madinatul Munawwaroh with a sample of 25 students from grades XI and XII who were given an animated video intervention about BSE. Sampling in this study used the Acidental Sampling technique. The analysis used was the Wilcoxon signed rank test. The results of this study were that the average knowledge score before (Pretest) being given animated video education was 7.12 and after (Posttest) being given animated video education was 16. The results of the bivariate analysis showed that there was an effect of animated video education on increasing self-examination knowledge in female students of MAS Madinatul Munawwaroh Bukittinggi (p-value: 0.000). Suggestions are that MAS Madinatul Munawwaroh Bukittinggi continues to facilitate its female students in gaining knowledge about health, especially about breast cancer prevention. Keywords: Education; video; breast self-examination; breast cancer.